Effect of ultrashort-acting β-blockers on 28-day mortality in patients with sepsis with persistent tachycardia despite initial resuscitation: a meta-analysis of randomized controlled trials and trial sequential analysis - Huang, Po; Liu, Fusheng; Hu, Xiao; Li, Bo; Xu, Xiaolong; Liu, Qingquan (Frontiers in Pharmacology, 2024)
The meta-analysis aims to identify whether patients with sepsis with persistent tachycardia despite initial resuscitation can benefit from ultrashort-acting β-blockers.The relevant studies from MEDLINE, Cochrane Library, Embase were searched by two independent investigators. RevMan Version 5.3 (The Cochrane Collaboration) was used for statistical analysis. Results: A total of ten studies were identified and incorporated into the meta-analysis. The results showed that the administration of ultrashort-Acting β-blockers (esmolol/landiolol) in patients with sepsis with persistent tachycardia despite initial resuscitation was significantly associated with a lower 28-day mortality (RR, 0.73; 95% CI, 0.57-0.93; P˂0.01). Subgroup analysis showed that the administration of esmolol in patients with sepsis was significantly associated with a lower 28-d mortality (RR, 0.68; 95% CI, 0.55-0.84; P˂0.001). While, there was no significant difference between the landiolol and control group (RR, 0.98; 95% CI, 0.41-2.34; P=0.96). No significant differences between the two groups were found in 90-day mortality, MAP, Lac, CI, and TnI at 24h after enrollment.The meta-analysis indicated that the use of esmolol in patients with persistent tachycardia, despite initial resuscitation, was linked to a notable reduction in 28-day mortality rates. Therefore, this study advocates for the consideration of esmolol in the treatment of sepsis in cases where tachycardia persists despite initial resuscitation.